Physicochemal and adhesion properties of soy protein based adhesives - Kim, Min Jung (Kansas State University, 2015)
Soy protein is one of the most promising bio-degradable adhesives as an alternative to synthetic petroleum-based adhesives for wood composite industries. In this study, soy protein was modified to improve adhesion properties and water resistance, which could facilitate the industrialization of soy protein-based adhesives. Furthermore, we attempted to identify a reliable indicator to predict the adhesion properties of soy protein by establishing the correlation of physical and mechanical properties with adhesion properties of soy protein. One of the objectives in this work was to investigate if inorganic calcium silicate hydrate (CSH) hybrids could improve adhesion properties of soy protein-based adhesives. 3-aminopropyltriethoxysilane (APTES) was used as a crosslinking agent between organic soy protein and inorganic CSH phases. APTES helped to form a crosslinked interface between soy protein and CSH, which was confirmed by changes in thermal, rheological, spectroscopic, and morphological properties with aging effect. More entangled structure and reduction of water-sensitive functional groups could lead to improvements in adhesion strength compared to unmodified soy protein-based adhesives. The second objective was to identify reliable indicators to predict shear adhesion properties by building the correlation between physical properties and adhesion properties of enzymatically modified soy protein-based adhesives (ESP). ESP was prepared with three independent variables (X1: trypsin concentration, X2: incubation time, and X3: glutaraldehyde (GA) concentration as a crosslinker) using a response surface methodology (RSM) called a central composite design (CCD). The important physical properties of viscosity (Y1), tacky force (Y2), and water resistance (Y3) were measured and investigated their relationship with adhesion strength. Viscosity, tacky force and water resistance showed solid correlation with adhesion strength of ESP and they were used to predict adhesion performance of soy protein modification system in this work. In addition, we studied the correlation between film strength and adhesion strength of another soy protein system. Because cohesion among protein molecules plays an important role in film and bonding mechanisms, we assumed that the film strength may be a reliable indicator to predict the adhesion strength of soy protein. The mechanical properties of the film and adhesion properties of soy protein on cherry wood were measured in terms of different concentrations of plasticizer (poly (propylene glycol) bis (2-aminopropyl ether) (H2N–PPG–NH2)). The results found out the low correlation between film and adhesion strength of soy protein in the presence of the plasticizer. We believe this might be caused by different curing conditions for film and adhesive applications of soy protein. Curing conditions greatly affect the thermal and curing behavior as well as mechanical properties of final materials. Thus, similar or comparable curing conditions should be required to obtain the information on the relationship between film and adhesion strength of soy protein.
Keywords: Adhesive; Soy protein; Materials Science (0794)